Neutrinoless Double Beta Decay Experiments With TeO2 Low-Temperature Detectors - Brofferio, Chiara; Cremonesi, Oliviero; Dell'Oro, Stefano (Frontiers in Physics, 2019)
Neutrinoless double beta decay (\bb) is a powerful tool for the investigation of Physics Beyond the Standard Model. The observation of \bb~would demonstrate that the lepton number is not a conserved quantity and it would provide us with precious information on the nature and mass of the neutrinos. Among the many experimental techniques used in the search for this rare process, low-temperature detectors represent one of the most promising choices: they show an excellent energy resolution and can scale to very large masses. In this work, we review the major experiments based on \ce{TeO_2} bolometers that were and continue to be carried out at the Laboratori Nazionali del Gran Sasso, Italy. This thirty-years-old effort on this front led to the construction of the CUORE detector, presently in data taking. The use of low-temperature detectors allows to study the \bb~of \ce{^{130}Te} on both ground and excited states, and to explore different decay mechanisms (``standard'' light neutrino exchange, Majoron emission, …). At the same time, more investigations of rare nuclear physics processes can also be performed, such as the two-neutrino double beta decay of \ce{^{130}Te} and other decays of tellurium (\ce{^{120}Te} and \ce{^{123}Te}). Looking towards a next-generation bolometric experiment, we highlight the challenges to be faced in order to further improve the sensitivity, focusing in particular on the background abatement